The effect of leadership on transformation of historically disadvantaged universities : the University of Limpopo experiences - Moikanyane, Khotso Keletso (My University, 2021)
Institutional transformation is a complex process that necessitates meticulous planning and management. As a result, it is imperative that an institution establishes effective leadership that will best steer the institution toward the desired objectives. Higher education and training is one sector that identified the need for transformation of its public tertiary institutions because of historical inequalities and imbalances, particularly with historically disadvantaged institutions. This magnitude prompted research on the effect of leadership on the transformation of historically disadvantaged institutions. The study used an exploratory sequential mixed-method approach that relied equally on primary and secondary data collection. Questionnaires, interviews, document analysis, and past publications were used to collect data that contributed to the study's conclusions. The findings of the study clearly show that effective leadership is a key factor in attaining the institution's transformational goals. The recommendations revealed that the institution's leadership should adopt a full transformational style of leadership qualities to ensure effective institutional transformation. This will provide the institution with greater opportunities and broaden its impact on society.
Thesis (MDev. (Planning and Management)) -- University of Limpopo, 2021
Keywords: Leadership; Transformation; Historically disadvantaged universities; University of Limpopo; Educational leadership -- South Africa; Education, Higher -- South Africa -- Congresses; Educational change -- South Africa -- Congresses